Solid-state NMR and powder XRD studies of the structure of SAPO-40 upon hydration-dehydration cycles - Lourenço, J. P. (2012)
It is well known that after the removal of the template many porous aluminophosphates and related materials are very sensitive to water.' Depending on the type of structure, reversible or irreversible phase transitions, loss of crystallinity and changes in the coordination of some framework A1 upon rehydration are observed. For example, solid-state NMR shows that the rehydration of SAPO-5 leads to the formation of octahedral Al. Subsequent dehydration restores the initial tetrahedral coordination of Al. Template-free SAPO-37 becomes totally amorphous to X-rays after exposure to water and stays so after subsequent thermal treatment^.,,^ In contrast, Barthomeuf and co-workers have shown recently, that, on hydration, template-free SAPO-34, an analogue of chabasite, shows the opening of some Si-0-A1 bonds, the effect being reversible upon dehydrati~n.T~h e hydrated distorted structure was found to be stable for months with no further modifications and the ordered material could be regenerated by removal of water. Here we wish to report that the structure of template-free SAPO-40 undergoes a similar reversible modification.